Use of medicines by patients of the primary health care of the Brazilian Unified Health System - Clarisse Melo Franco Neves Costa; Micheline Rosa Silveira; Francisco de Assis Acurcio; Augusto Afonso Guerra Junior; Ione Aquemi Guibu; Karen Sarmento Costa; Margô Gomes de Oliveira Karnikowski; Orlando Mario Soeiro; Silvana Nair Leite; Ediná Alves Costa; Renata Cristina Rezende Macedo do Nascimento; Vânia Eloísa de Araújo; et al. (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE To characterize the use of medicines by patients of the primary health care of the Brazilian Unified Health System (SUS). METHODS This is a cross-sectional, exploratory, and descriptive study, part of the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos - Serviços, 2015 (PNAUM - National Survey on Access, Use and Promotion of Rational Use of Medicines - Services, 2015). Interviews were carried out with patients present in the services by semi-structured questionnaires. Sociodemographic, clinical, and use of medicines variables were assessed and the use of medicines in the 30 days prior to the interview was also verified. The population was stratified into three age groups: 18 to 44, 45 to 64, and 65 years or more. The differences between the age groups were verified using the Student's t-test for continuous variables and chi-square test for the categorical ones. The complex samples analysis plan was employed. The medicines were classified according to the Anatomical Therapeutic Chemical Classification System. RESULTS Of the 8,803 patients interviewed, 6,511 (76.2%) reported to have used medicines in the 30 days prior to the interview. On average, each patient used 2.32 medicines, without difference between the sexes. Among medicine users, 18.2% were aged 65 years or more. Compared to the other age groups, older adults presented more comorbidities, used more medicines, and self-reported worse health conditions. They were also less educated, reported worse economic situation, and lived alone. The medicines that were mostly used were "other analgesics and antipyretics" (3rd ATC level) and Losartan (5th ATC level). CONCLUSIONS Most medicine users had lower education level and presented comorbidities. The most used medicines were the antihypertensive ones. Self-medication was higher among young people. Most patients reported to use generic medicines. The average number of medicines and the prevalence of use increased with age. Due to the characteristics observed and the difficulties in the use of medicines, older adults are in a situation of greater vulnerability.